1040 Evaluation of The Use of Biopatch In Haemodialysis Lines: Are We Reducing the Risk of Infection?. (12th October 2021) - Win, M; Banerjee, D; Deng, J; Fraser, N
Abstract: Aim: Children who had the central venous lines inserted for prolonged vascular access usually experience the catheter-related blood stream infection (CRBSI). CRBSI is known to be associated with high morbidity which increases the cost of the healthcare and the chances of mortality. Clinical evidence suggests that the use of biopatch (chlorhexidine-impregnated dressing) is effective in reducing the rate of infection in central venous lines. The aim of our study was to evaluate whether the use of biopatch actually reduced the CRBSI in children who had had haemodialysis lines at our institution. Method: Theatre logs and electronic records of 46 patients who had haemodialysis lines inserted between 2015-2019 were retrospectively reviewed. These patients were randomly selected. Results: The total number of lines inserted in 46 patients were 104. The mean of line per patient was 2.2. Out of 104 lines, 22 lines (21%) had confirmed infection. 6 (27%) infected lines used biopatch while 16 (73%) did not use biopatch as per the documentation in the records. Staphylococcus aureus (40%) and coagulase negative staphylococcus (22%) were the main source of these line infections. Conclusions: Infection of the central line is still a significant problem. Infections were more prevalent in cases which did not use biopatch according to the documentation. We believe the rate of infection can be reduced by encouraging the use of biopatch on regular basis for the haemodialysis lines and the proper documentation of its use in the operation notes.